Window to His World: Using a Patient's YouTube Channel to Help Diagnose Chronic Mania. Issue 4 (July 2020) - INCE, H. YAVUZ; STREETER, CALE C.; MAKSIMOWSKI, MICHAEL
Abstract : Although chronic mania has been investigated, with several case reports and systematic retrospective cohort studies in the literature, it not a widely recognized entity. No specific definition for chronic mania is provided in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Furthermore, it is challenging to identify patients with chronic mania unless they come to the attention of the legal or medical system. We present the case of a manic patient who was hospitalized and subsequently found to have a YouTube channel that he had been using to promote his self-invented religion for over 2 years. Consent was obtained from the patient to review this YouTube channel for collateral information. From these videos, the patient was seen to be chronically circumstantial in his thought processes, grandiose in his ideas, highly energetic, distractible, preoccupied with religion, and talking with elaborate and rapid speech. A significant improvement in his symptoms was observed after administration of oral risperidone, with his scores on the Young Mania Rating Scale and Brief Psychiatric Rating Scale also showing improvement. To our knowledge, this is the first case in the literature in which an online video-sharing service was used longitudinally to facilitate diagnosis of a mental illness. We suggest that technology has great potential to improve our diagnostic tools, especially for disorders such as chronic mania the diagnosis of which relies primarily on self-report and collateral information.